Remaja Wanita: Self regulation dan Impulsive buying Produk Skincare di Online Shop - Reny Yuniasanti; Ayu Annora Azaria (Universitas Kristen Maranatha, 2024)
The growth of e-commerce trade makes it easier for people to shop more easily and flexibly, anytime and anywhere. The aim of this research is to determine the relationship between self-regulation and impulsive buying of skincare products in online shops among female teenagers. The proposed hypothesis is that there is a negative relationship between self-regulation and impulsive buying of skincare products in online shops among female teenagers. The subject criteria in this study were female teenagers aged 17-22 years who purchased skincare products in online shops 2 to 5 times in 1 month. The number of subjects in this research was 100 people using probability sampling. Data collection uses a self-regulation scale and an impulsive buying scale. With the resulting coefficient (rxy) = -0.584 with a significance value of p = 0.000 (p < 0.050). The coefficient of determination (R2) obtained is 0.341, which shows that the self-regulation variable has a contribution of 34% to the variable impulsive buying of skincare products in female teenagers and 66% is influenced by other factors. The benefit of this research is to provide information regarding self-regulation for purchasing behavior in online shopping, especially skincare products.